Virtual Reality-Based Learning Media for Food Chain Adventures to Improve Students’ Science Learning Outcomes - Yuliana Tri Widyaningrum; Yulianto, Sigit (Jurnal Edutech Undiksha, 2025)
Science (IPAS) is often considered difficult by students, which is caused by a lack of innovative teaching methods. Therefore, new innovations in the learning process are needed. This study aims to develop a virtual reality-based food chain adventure media to improve elementary school students’ science learning outcomes. This research is a development study using the Borg and Gall model. The subjects of the study included learning media experts, content experts, and classroom teachers. The trial subjects consisted of 6 fifth-grade students for the small group trial and 22 fifth-grade students for the large group trial. Data were collected through observation, interviews, documentation, questionnaires, and tests. The instruments used in the study were questionnaires and tests. Data were analyzed using qualitative and quantitative descriptive analysis and t-tests. The results showed that the virtual reality-based food chain adventure media was rated as “highly feasible” by both media and content experts. Students’ responses also fell into the “highly feasible” category. From the pretest and posttest results involving 28 students, the t-test calculation indicated that the media had a significant effect on students’ learning outcomes. It can be concluded that the virtual reality-based food chain adventure media can improve the science learning outcomes of fifth-grade students. The implications of this study are that the media can enhance student learning outcomes, motivate teachers to develop innovative learning media, and serve as a reference for developing effective teaching strategies.